The Afsluitdijk as a Complex System. Issue 1 (29th May 2019) - Vogt, Berber
ABSTRACT: The Netherlands government authorized the Afsluitdijk (enclosure dam) in 1918 and the structure was completed in 1932. The objective was to provide better protection of the hinterland against flooding and to reclaim new land from the sea. The damming of the Zuiderzee by the Afsluitdijk created a freshwater reservoir and enabled a traffic connection between the provinces of North Holland and Friesland. Environmental protection and sustainability factors increased in importance the over years as a result of climate change. One critical objective is guaranteeing the safety of the hinterland (keeping our feet dry). In order to achieve this objective, the Afsluitdijk as a system needs to have the right capabilities and the corresponding functions to be able to protect the hinterland. In order to bring the various stakeholders on board, we use a model known as strategic environmental management (SEM, Dutch: SOM) that involves stakeholders at the outset of a project and we perform a stakeholder/environmental analysis to gather information about the various needs. The Rijkswaterstaat (the Directorate‐General for Public Works and Water Management) then carries out a prioritization process to determine the needs to be included in the on‐site development of the system.